AIDS and human rights in the European community - Carle, Pia; Hendriks, Aart; Zeegers, Dineke (Luxembourg: Commission of the European Communities, 1991)
"Pia Carle; Aart Hendriks; Dineke Zeegers Fonds Suzan Daniel (FSD)"